2006
DOI: 10.1183/09031936.06.00009405
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of tracheostomy phonation valves

Abstract: Phonation valves are commonly used devices that allow the restoration of speech in tracheostomised patients. However, their use should not compromise the physiological benefit of tracheostomy.Six commercialised phonation valves were studied in a dynamic set-up simulating a respiratory frequency of 20 breaths?min . Additional WOB varied with a ratio of 4.4 between the best and the worst valve. While the different clinical conditions did not modify respiratory patterns and gas exchanges, a significant effect on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 35 publications
0
13
0
3
Order By: Relevance
“…Although imposed WOB may not generate respiratory muscle fatigue in patients without respiratory insufficiency, it may cause discomfort. For example, the levels of imposed WOB seen with some of the devices tested here were associated with major increases in respiratory discomfort in tracheostomized patients [13]. However, data from these patients with severe chronic respiratory failure may not apply to patients with OSA, whose daytime respiratory function is often normal.…”
Section: Discussionmentioning
confidence: 85%
“…Although imposed WOB may not generate respiratory muscle fatigue in patients without respiratory insufficiency, it may cause discomfort. For example, the levels of imposed WOB seen with some of the devices tested here were associated with major increases in respiratory discomfort in tracheostomized patients [13]. However, data from these patients with severe chronic respiratory failure may not apply to patients with OSA, whose daytime respiratory function is often normal.…”
Section: Discussionmentioning
confidence: 85%
“…After educating referring hospitals about tracheostomy tube manometry, they started to use speaking valves with non‐fenestrated tubes. (8) While capping has been recommended only with fenestrated tubes or non‐fenestrated No. 4 tubes, (9) we found that many patients tolerated capping with other tubes.…”
Section: Discussionmentioning
confidence: 99%
“…This ensures that sufficient subglottic pressure is maintained during both the inspiratory and expiratory ventilator cycles for voice production. While a range of tracheostomy speech valves are available (Prigent et al 2006), only two are US Food and Drug Administration (USFDA) approved for use with a ventilator (Vent‐Trach, Boston Medical Products, Boston, MA, USA [http://www.bosmed.com]; and the Passy–Muir Tracheostomy Speaking Valve (PMTSV); Passy–Muir Inc., Irvine, CA, USA [http://www.passy-muir.com]) with the PMTSV being the most commonly used clinically and in previous research (Dikeman and Kazandjian 2003). In addition to allowing production of complete sentences (Manzano et al 1997), the PMTSV has been reported to improve speech flow, volume, voice quality and speech intelligibility (Passy et al 1993).…”
Section: Introductionmentioning
confidence: 99%